SPREAD OF EUROPEAN ASH IN FOREST STANDS OF THE FOREST-STEPPE PART OF KHARKIV REGION - Borysova, V. L. (Forestry and Forest Melioration, 2018)
Introduction European ash (Fraxinus excelsior L.: Oleaceae) is a component of forest and protective stands and widely used in gardening. Recently, in many regions health condition of ash stands becomes worse in the result of adverse weather conditions, damage by insects and diseases, particularly Hymenoscyphus fraxineus, which brought to ash decline in the large area. As health condition of ash differs by regions and forest site conditions, it is necessary to reveal, what conditions are favorable for a spread and intensive development of its deterioration. It will give the possibility to develop effective measures to mitigate the negative consequences for ash stands. Stand structure is one of the factors affecting the spread of injurious organisms and tree susceptibility to damage or disease. Therefore it was necessary to analyze the forest fund of different regions. The aim of the research was to reveal the peculiarities of European ash spread in the forest stands of the forest-steppe part of Kharkiv region. Materials and Methods In order to identify the peculiarities of spread of European ash in the forest stands of the forest-steppe part of Kharkiv region, the database of Production Association “Ukrderzhlisproekt” was analyzed concerning forest fund of Forest State Enterprises (SE) of Kharkiv region, located in the Left-bank Forest Steppe (SE “Vovchanske Forest Economy”, “Gutyanske Forest Economy”, “Zhovtneve Forest Economy”, “Zmiyivske Forest Economy” and “Chuguevo-Babchanske Forest Economy”). The forest plots with European ash as the main forest forming species were selected from the database for each Forest Enterprise. These data were grouped by the types of forest site conditions, origin, age, the density of stocking, tree species composition, bonitet class, and respective distribution of ash stands area was evaluated. Results and Conclusions For the whole region and every Forest State Enterprise, the part of ash stands area from all deciduous stands area (0.72 %), the part of natural vegetative (70.6 %), natural seed (3 %) and artificial (26.3 %) ash stands was calculated. Ash stands grow mainly in the fresh maple & lime oak stands (81.9 %) and in dry maple & lime oak stands (13.8 %). Mixed ash stands of middle age and with the density of stocking 0.7–0.9 dominate. Artificial ash stands are characterized mainly by the I bonitet class, and natural ash stands are characterized mainly by the II bonitet class.